PEMANFAATAN SUMBER BELAJAR DALAM PROSES PEMBELAJARAN - Supriadi Supriadi (UIN AR-RANIRY, 2015)
Learning resource is anything tangible objects and people that can support learning so as to include all possible sources can be utilized by faculty in order to study the behavior occurs. factors that encourage students and faculty in selecting and utilizing a variety of learning resources, namely: (1) Internal is awareness, motivation, interests, abilities, and comfort within the user, and (2) External is the availability of learning resources, variations learning resources, the quantity of learning resources, the quality of learning resources, ease of access to learning resources, forms and types of learning resources, learning, space, human resources, as well as the traditions and the prevailing system of educational institutions. There is a tendency to use a variety of learning resources in the educational unit is influenced by two main factors, namely internal factors and external factors. Internal factors are the dominant influence awareness, passion, interests, abilities, and comfort in the user himself. In terms of external factors that influence the availability of varied learning, learning resources quantity, ease of access to learning resources, learning, space, human resources, as well as the traditions and the system being applicable in educational institutions.